The Sacred Architecture of Josep Lluís Sert - Iñigo Ugalde-Blázquez; Ricardo Gómez-Val; Cinta Lluis-Teruel; Pilar Moran-García (Religions)
An unknown aspect of Josep Lluís Sert (Barcelona, 1902–1983) is his deep engagement with Christian spirituality, particularly following his American exile. This perspective is beautifully reflected in his religious-themed projects, among which historiography has highlighted the church of Puerto Ordaz (Venezuela, 1951), the Chapel of St. Botolph (Boston, 1963–1968), and the Carmel de la Paix Chapel (Mazille, 1967–1972), designed, respectively, before, during, and after the Second Vatican Council. Using these three well-known projects as a starting point, our aim is to expand the discussion around this topic to encompass the entirety of Sert’s sacred architecture. The contributions of Sert to the design of modern religious architecture are analyzed in this study, firstly through the distinctive aspects of his architecture, such as its urban scale and interactions between various plastic arts, and secondly through his theological references. This study is based on Sert’s original drawings, as well as specific bibliographic sources and articles from specialized journals. At the same time, it seeks to highlight an aspect of the architect that, despite the significance and brilliance of his designs, has received little attention until now.